Control of Nitrogen Inhomogeneities in Type-I and Type-II GaAsSbN Superlattices for Solar Cell Devices - Nazaret Ruiz; Verónica Braza; Alicia Gonzalo; Daniel Fernández; Teresa Ben; Sara Flores; José María Ulloa; David González (Nanomaterials, 2019)
Superlattice structures (SLs) with type-II (GaAsSb/GaAsN) and -I (GaAsSbN/GaAs) band alignments have received a great deal of attention for multijunction solar cell (MJSC) applications, as they present a strongly intensified luminescence and a significant external quantum efficiency (EQE), with respect to the GaAsSbN bulk layers. Despite the difficulties in characterizing the distribution of N in dilute III-V nitride alloys, in this work we have obtained N-compositional mappings before and after rapid thermal annealing (RTA) in both types of structures, by using a recent methodology based on the treatment of different scanning transmission electron microscopy (STEM) imaging configurations. Texture analysis by gray level co-occurrence matrixes (GLCM) and the measurement of the degree of clustering are used to compare and evaluate the compositional inhomogeneities of N. Comparison with the Sb maps shows that there is no spatial correlation between the N and Sb distributions. Our results reveal that a better homogeneity of N is obtained in type-I SLs, but at the expense of a higher tendency of Sb agglomeration, and the opposite occurs in type-II SLs. The RTA treatments improve the uniformity of N and Sb in both designs, with the annealed sample of type-II SLs being the most balanced structure for MJSCs.